CHANGE IN FUNCTIONAL PARAMETERS OF PLATELETS IN TUBAL PREGNANCY IN VARIOUS CLINICAL SITUATIONS - Максим Игоревич Соснин; Елена Николаевна Кравченко; Ольга Михайловна Ларионова; Олег Александрович Неверовский; Ольга Евгеньевна Кубиц (The Publishing House Medicine and Enlightenment, 2018)
The aim - to assess the changes in serum platelet counts, such as the average platelet count (MPV), platelet width (PDW), and discuss the mechanism of these changes in tubal pregnancy in early gestation in various clinical situations. Materials and methods. A retrospective study of 90 clinical cases of tubal pregnancy, 25 observations with a rupture of the fallopian tube (PMT), 65 patients with progressive tubal pregnancy (PTB) was carried out. In 31 pregnant women, at terms up to 4-5 weeks, with positive β-hCG, no ultrasound signs of uterine pregnancy were observed. The study was conducted in the period from 2012-2016. Results. MPV was lower in the group with PTB, especially with PMT, but higher in patients who did not have ultrasound signs of uterine pregnancy in the early stages, compared to those in the control group. The highest PDW values were higher at RMT. The conclusion.The number of platelets was significantly lower in situations with PMT compared with the PGT and the control group. A more pronounced inflammation reaction occurs in clinical cases with PMT, which may contribute to lower MPV values and an increase in PDW.